Hypokalemic quadriparesis due to renal tubular acidosis in a patient with Sjögren’s syndrome: A case series - Maskey, Abhishek; Singh, Neeraj; Gautam, Santosh; Bhattarai, Prashant; Poudyal, Prakash; Manandhar, Dhiraj Narayan; Chhetri, Pramod Kumar (Journal of Advances in Internal Medicine, 2014)
We report two cases of female patients presented with hypokalemia secondary to renal tubular acidosis. Sjögren’s syndrome was diagnosed in both the patients on the basis of histopathological and autoantibodies tests. The patients were treated with potassium and bicarbonate supplementation. Renal involvement in Sjögren’s syndrome is not uncommon and may precede sicca complaints. The pathology in most cases is a tubulointerstitial nephritis causing distal renal tubular acidosis and rarely, hypokalemic paralysis. The complications of renal tubular acidosis include life threatening hypokalemia, nephrolithiasis, chronic renal failure, growth retardation and osteomalacia. These consequences can be avoided if the diagnosis is made early and lifelong potassium and alkali supplementation is initiated. Primary Sjögren’s syndrome should be considered in women with acute weakness and hypokalemia. DOI: http://dx.doi.org/10.3126/jaim.v3i1.10701 Journal of Advances in Internal Medicine 2014;03(01):30-33